Investigation of Beraprost Sodium on Cardiac Function and Hemodynamics in Canine Models of Chronic Pulmonary Hypertension - Suzuki, Ryohei; Yuchi, Yunosuke; Saito, Takahiro; Teshima, Takahiro; Matsumoto, Hirotaka; Koyama, Hidekazu (Frontiers in Veterinary Science, 2022)
Pulmonary hypertension (PH) is a life-threatening disease in dogs characterized by increased pulmonary arterial pressure (PAP) and/or pulmonary vascular resistance. No study has evaluated the utility of beraprost sodium (BPS) in dogs with PH. This study aimed to evaluate the effect of BPS on cardiac function and hemodynamics and examine the optimal dose of BPS in canine models of chronic embolic PH. In this prospective crossover study, three doses of BPS (5, 15, and 25 µg/kg, twice a day) were examined in eight canine models of chronic embolic PH. All model dogs underwent invasive PAP measurement, echocardiography, and noninvasive systemic blood pressure measurement before and after continuous administration of oral BPS for one week. No side effects of BPS were observed in any dog during the study. All doses of BPS significantly decreased systolic PAP and pulmonary vascular impedance. Additionally, systemic vascular impedance significantly decreased with 15 and 25 µg/kg of BPS. The right ventricular stroke volume and longitudinal strain significantly decreased with all doses of BPS. The left ventricular stroke volume and circumferential strain decreased with 15 µg/kg BPS. BPS was well tolerated in this study. A dose-dependent vasodilating effect on pulmonary vessels was observed in canine models of chronic PH. Additionally, 15 µg/kg BPS showed a balanced vasodilating effect on systemic and pulmonary vessels. Furthermore, with a decrease in systemic and pulmonary vascular impedance, the left and right ventricular functions were significantly improved. Our results suggest that BPS may be useful in the treatment of canine PH.